Relación entre estrés académico y el rendimiento académico de tercero bachillerato general unificado en la unidad educativa réplica Nicolás Infante Díaz: desde el enfoque psicopedagógico. - Moran Salazar, Nicole Jamileth (2025)
The research entitled “Relationship Between Academic Stress and Academic Performance of Third-Year General Unified Baccalaureate Students at the Unidad Educativa Réplica Nicolás Infante Díaz from a Psychopedagogical Perspective” was based on the premise that academic stress, conceived as a psychological and adaptive response to educational demands, could become a determining factor affecting academic performance. The general objective was to analyze the relationship between academic stress and academic performance of Tercero de Bachillerato General Unificado students at Unidad Educativa Réplica Nicolás Infante Díaz, from a psychopedagogical perspective. The methodology adopted a positivist paradigm, with a quantitative approach and correlational level. The population consisted of 60 students, and the sample, selected by convenience, included 53 participants. To measure academic stress, the SISCO SV-21 Inventory by Barraza was applied, while academic performance was assessed through the grades of the first trimester of the 2025–2026 school year. The results showed that 56.6% of students presented a moderate level of academic stress, followed by 39.6% with a severe level and only 3.8% with a mild level. Regarding performance, 54.7% achieved the required learning outcomes (grades 7–8), and 45.3% mastered the required learning outcomes (grade 9), reflecting an overall optimal academic performance. The Spearman analysis showed a very weak positive correlation (ρ = 0.131) and not significant (p = 0.349) between both variables, so it could not be affirmed that the level of stress directly influenced academic performance. Finally, it was concluded that there is no significant relationship between both variables; however, it is necessary to provide psychopedagogical strategies for the reduction and management of academic stress.